Hochfeld, Marion County - Lehrman, Samuel W. (Kansas State University, The Chapman Center for Rural Studies, 2012)
The village of Hochfeld, located in the Menno Township of Marion County, Kansas, was settled in 1874 by German Mennonites on land purchased from the Atchison, Topeka, and Santa Fe Railroad Company. Attracted by military exemption laws and new opportunities in Kansas, the larger Alexanderwohl Community brought traditions such as land partibility to a new home in the Cottonwood Valley. This study includes an interview, analysis of early maps of the county, census research, and etchings of Hochfeld in Marion County, Kansas.
Samuel W. Lehrman, “Hochfeld, Marion County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/110.
Keywords: Cottonwood Creek; Goessel; Hochfeld; Marion County; winter wheat; Alexanderwohl Mennonite Church